Pembiasaan Nilai Keislaman dalam Kegiatan Pembiasaan di TKIT Baitul Izzah Kota Bengkulu - Salsa Sabina Zia; Henny Kurnia Agustina; Fatimah Tusya Diah; Intan Ria Juwita Putri; Deni Febrini (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Integrated Islamic Early Childhood Education (PAUD IT) Baitul Izzah Bengkulu is an Islamic-based educational institution that integrates a holistic curriculum grounded in Islamic morals with the national curriculum to shape superior, creative, independent, and noble-charactered generations from an early age. Located within the Great Mosque Baitul Izzah complex in Bengkulu City, the institution aims to prosper the mosque as a center for religious learning, introduce children to the mosque environment, and provide high-quality Islamic education amid the growing public demand for Islamic schools. This institution emphasizes the development of religious character, social skills, and cognitive abilities in a balanced manner. Through five core missions fostering love for Allah SWT and Prophet Muhammad SAW in daily learning activities, educating children intelligently and creatively, facilitating children’s potential and talent development, implementing enjoyable and child-centered learning methods, and continuously enhancing the quality of human resources PAUD IT Baitul Izzah actively supports early character building that is consistently aligned with Islamic values and educational goals.